2015
DOI: 10.1007/s12155-015-9647-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Characterization of Lignin from Cardoon (Cynara cardunculus L.) Stalks

Abstract: The lignin from Cynara cardunculus stalks was isolated by the classical Björkman method and characterized by pyrolysis coupled with gas chromatography and mass spectrometry (Py-GC/MS), two-dimensional nuclear magnetic resonance spectroscopy (2D-NMR), and derivatization followed by reductive cleavage (DFRC). The milled Cynara lignin (MCyL) was constituted mainly by guaiacyl (G) and syringyl-units(S) (S/G molar ratio of 0.7), with the complete absence of p-hydroxyphenyl (H) units. The 2D-NMR analysis indicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
4
15
0
Order By: Relevance
“…To investigate the structural characteristics of DES-lignin, 2D-HSQC NMR for DES-lignin sample (D 12h ) extracted from willow by DES-treatment at 120 °C for 12 h and the EMAL of willow were obtained (Figure 4). Assignment of the peaks in the 2D-HSQC NMR spectra was conducted based on previous reports [32,43,44,45]. The peaks corresponding to methoxyl (3.81/56.7 parts per million (ppm)) and β-aryl ether are shown for A α (4.91/70.3 ppm) and A γ (4.05/87.5 ppm), β–β are shown for C α (4.71/86.1 ppm), C β (3.08/53.9 ppm) and C γ (4.11/70.3 ppm), guaiacyl (G 5/6 , 6.79/115.1 ppm), syringyl (S 2/6 , 6.61/102.9 and 7.19/116.2 ppm), and p -hydroxybenzoate (P 2/6 , 7.61/131.2 ppm) appeared in the DES-lignin (D 12h ) NMR spectrum indicating functional groups associated with lignin were present and not severely damaged during DES treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the structural characteristics of DES-lignin, 2D-HSQC NMR for DES-lignin sample (D 12h ) extracted from willow by DES-treatment at 120 °C for 12 h and the EMAL of willow were obtained (Figure 4). Assignment of the peaks in the 2D-HSQC NMR spectra was conducted based on previous reports [32,43,44,45]. The peaks corresponding to methoxyl (3.81/56.7 parts per million (ppm)) and β-aryl ether are shown for A α (4.91/70.3 ppm) and A γ (4.05/87.5 ppm), β–β are shown for C α (4.71/86.1 ppm), C β (3.08/53.9 ppm) and C γ (4.11/70.3 ppm), guaiacyl (G 5/6 , 6.79/115.1 ppm), syringyl (S 2/6 , 6.61/102.9 and 7.19/116.2 ppm), and p -hydroxybenzoate (P 2/6 , 7.61/131.2 ppm) appeared in the DES-lignin (D 12h ) NMR spectrum indicating functional groups associated with lignin were present and not severely damaged during DES treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Lignin content in the stalks varies from 16.4 to 19.2% [131,134,135]. The lignin monomeric composition of cardoon stalks separated in depithed and pith regions shows a H:G:S relation of 1:6:8 and 1:4:9, respectively, determined by Py-GC/MS (FID), corresponding to a S/G ratio of 1.3 and 2.2, respectively [136]. Whole stalks lignin was studied after isolation by the Bjӧrkman method and characterized by Py-GC/MS, 2D NMR and DFRC' [136].…”
Section: Cynara Cardunculusmentioning
confidence: 99%
“…The lignin monomeric composition of cardoon stalks separated in depithed and pith regions shows a H:G:S relation of 1:6:8 and 1:4:9, respectively, determined by Py-GC/MS (FID), corresponding to a S/G ratio of 1.3 and 2.2, respectively [136]. Whole stalks lignin was studied after isolation by the Bjӧrkman method and characterized by Py-GC/MS, 2D NMR and DFRC' [136]. The 2D NMR analysis showed that the isolated lignin has a H:G:S relation of 0:58:42, i.e., a S/G ratio of 0.7 and a predominance of β-O-4′ alkyl-aryl ether structures (70% of all inter-unit linkages), followed by a considerable amount of condensed structures: phenylcoumarans (β-5′, 14%), resinols (β-β′, 7%), spirodienones (β-1′, 5%) and dibenzodioxocins (5-5′, 4%).…”
Section: Cynara Cardunculusmentioning
confidence: 99%
See 1 more Smart Citation
“…The lignin present in the whole stalks was studied after isolation by the Bjӧrkman method (MCyL) and characterized by Py-GC/MS [72]. In general, there was a similar distribution of the lignin-derived compounds formed during pyrolysis of MCyL comparatively to depithed and pith samples pyrolysis, and the G units were released in higher abundances than the respective S units, attaining an S/G molar ratio 0.3.…”
Section: Cynara Cardunculusmentioning
confidence: 99%